Open cystogastrostomy in the management of a large pancreatic pseudocyst in a child - Moaied A. Hassan (Elsevier, 2020)
Pancreatic pseudocyst is the most common cystic lesion of the pancreas. Unlike in adults, where gall stones and alcohol are the most common etiology, trauma is the leading cause of pancreatic pseudocyst in children. Most pancreatic pseudocysts in children resolve spontaneously with conservative management. Lesions that are symptomatic, larger than 6 cm in diameter, or persist for 6 weeks or more following the initial insult, usually require some sort of therapeutic intervention. Therapeutic interventions vary depending on the cyst's nature and position, presence of complications and surgeon's experience. These include percutaneous drainage, endoscopic drainage and surgical drainage by laparotomy or recently by laparoscopy. We present a nine years old male child with large pancreatic pseudocyst following blunt abdominal trauma. We discuss the mode of presentation, diagnostic evaluation and therapeutic intervention that has been done to treat him.